(untitled) (Encuentros, 2023)
The purpose of this scientific research product is to develop a methodological route for the design and implementation of learning outcomes in the Nursing program of the Popular University of Cesar. The research had a qualitative approach, using the documentary review technique of a bibliographic type, and as an instrument, a data collection form was used for the elaboration of comparative matrices, whose central axes were international and national guidelines for the construction of learning results. , the competencies and profile of the nursing profession. In addition, a review of articles was carried out in the databases: Scielo, Science Direct, Scopus, LILACS, and PubMed, as a reference framework for the design of a methodological route, which integrates problematizing nodes in each of the study plan areas. , with the programmatic contents, the academic activities, and the learning results, which contribute to the development of competencies and compliance with the graduation profile of the nursing profession.